Correlates of verbal and physical violence experienced and perpetrated among cisgender college women: serial cross-sections during one year of the COVID-19 pandemic - Theodore, Deborah A.; Heck, Craig J.; Huang, Simian; Huang, Yuije; Autry, April; Sovic, Brit; Yang, Cynthia; Anderson-Burnett, Sarah Ann; Ray, Caroline; Austin, Eloise; Rotbert, Joshua; Zucker, Jason; et al. (Frontiers in Reproductive Health, 2024)
IntroductionViolence against women is a prevalent, preventable public health crisis. COVID-19 stressors and pandemic countermeasures may have exacerbated violence against women. Cisgender college women are particularly vulnerable to violence. Thus, we examined the prevalence and correlates of verbal/physical violence experienced and perpetrated among cisgender women enrolled at a New York City college over one year during the COVID-19 pandemic.MethodsFrom a prospective cohort study, we analyzed data self-reported quarterly (T1, T2, T3, T4) between December 2020 and December 2021. Using generalized estimated equations (GEE) and logistic regression, we identified correlates of experienced and perpetrated violence among respondents who were partnered or cohabitating longitudinally and at each quarter, respectively. Multivariable models included all variables with unadjusted parameters X2p-value ≤0.05.ResultsThe prevalence of experienced violence was 52% (T1: N = 513), 30% (T2: N = 305), 33% (T3: N = 238), and 17% (T4: N = 180); prevalence of perpetrated violence was 38%, 17%, 21%, and 9%. Baseline correlates of experienced violence averaged over time (GEE) included race, living situation, loneliness, and condom use; correlates of perpetrated violence were school year, living situation, and perceived social support. Quarter-specific associations corroborated population averages: living with family members and low social support were associated with experienced violence at all timepoints except T4. Low social support was associated with higher odds of perpetrated violence at T1/T3. Other/Multiracial identity was associated with higher odds of violence experience at T3.ConclusionsLiving situation was associated with experienced and perpetrated violence in all analyses, necessitating further exploration of household conditions, family dynamics, and interpersonal factors. The protective association of social support with experienced and perpetrated violence also warrants investigation into forms of social engagement and cohesion. Racial differences in violence also require examination. Our findings can inform university policy development on violence and future violence research. Within or beyond epidemic conditions, universities should assess and strengthen violence prevention and support systems for young women by developing programming to promote social cohesion.